Brickwork for apprentices - Hodge, J. C. (John Charles); Thorpe, M. (Malcolm) (London : Routledge, 2020)
Expanded and edited by Malcolm Thorpe, a former CITB Advisor, this latest edition incorporates all the latest industry-based requirements and technical developments in the construction industry. A new feature is the e-resource facility that includes multiple choice questions and answers, short oral questions and answers, and practical competency checks with marking schemes. These are all matched to current programmes, providing students with essential practice and revision for exam preparation. A classic text, Brickwork for Apprentices has been the established reference on brickwork for generations of bricklayers. Continuously in print since 1944, John Hodge's classic text has now been revised in its sixth edition and brought fully in line with the latest Building Regulations and requirements for City & Guilds courses. This is an essential text for qualified bricklayers and other professionals working in construction, as well as students new to the industry and wishing to embark on a career in bricklaying.
OCLC-licensed vendor bibliographic record.
Keywords: Bricklaying; TECHNOLOGY / Construction / General